THE SHAPE OF CUSTOMER (MEMBER) VALUE ON CO-OPERATIVE COMPANY (CO-OPERATIVE) - Rizal Ramdan Padmakusumah (Journal of International Conference Proceedings (JICP), 2018)
The purpose of this paper is to know the shape of member value on the co-operative. Descriptive analysis used in this research which are conducted on the following sources such as national-international journals, national-international seminars proceedings, scientific books, and professional experiences. The results of the study indicate that a new definition of member value has been established. Member value dimensions consists of attributes benefits, outcomes benefits, monetary costs, and non-monetary costs. Member value has an influence on member satisfaction, member loyalty, and co-operative performance. The implications of this study are the dimensions and indicators in this study can be tested empirically in subsequent research. Co-operative managers can try to use its to improve the superior customers value on their cooperatives. . Keywords: customer, member, value, dimension, indicator, co-operative, company